Analisis Kelembagaan Dan Strategi Peningkatan Daya Saing UMKM Emping Melinjo Di Kabupaten Magetan - Fajar Kurnia Mustaqim; Kusnandar Kusnandar; Agustono Agustono (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2018)
This study aims to analyze institutional melinjo chips MSMEs, identify internal and external factors, formulate strategies for improving the competitiveness of melinjo chips MSMEs, and prioritizing strategies for improving the competitiveness of melinjo chips MSMEs in Magetan regency. The research methods used include: Descriptive Analysis, SWOT Analysis, SWOT matrix, and AHP. The results showed that: (1) there are 4 structure of the supply chain in the distribution of products chips melinjo, and the main institutional sectors in improving the competitiveness of melinjo chips MSMEs, namely the public  sector,  voluntary  sector  and  private  sector;  (2)  identification  of  internal  and external factors obtained strengths, weaknesses, opportunities and threats in improving the competitiveness of melinjo chips MSMEs; (3) matrix SWOT produced 10 alternative strategies to increase competitiveness; (4) priority strategy in improving the competitiveness of melinjo chips MSMEs is provide training and guidance to the next generation  about  the  importance  of  business  continuity  that  has  quality  products according  to  market  demand,  establish  cooperation  with  suppliers  to  ensure  theavailability of raw materials; and improve product quality and maximum service to maintain consumer confidence.